The interdisciplinarity in the field Education from Municipal Elementary School José Paim de Oliveira – Santa Maria/RS (Research, Society and Development, 2020)
The article shows reflections concerning the scholar management and the curricula of a field school by the eyes of interdisciplinarity. The study done is a result of a master’s research from the first author and raises discussion about the Pedagogical Proposal of this public teaching institution located in the city of Santa Maria, RS. This way, it is analyzed the constructions done to the context in which the school is inserted, and the interdisciplinary practices realized in the school from reflexive and formative conversation circles proposed to the educators and managers of the school. The research has a qualitative approach and of a case study. The Conversation Circles were done with all educators from the school, from Children’s Education, Lower Elementary School, Upper Elementary School and the school managers. The results show that the school has a history of valuing the knowledge from the field and from the community to which it is part of, with coherent and contextualized activities. It is concluded that the educators and the school community demonstrate in their actions, the feeling of belonging to the field school Project, based on respect, collaboration and collective commitment of all involved, showing that it is possible to make the difference in education and in the quality of the teaching to be offered.